Improvement of phytase biosynthesis by new bacterial isolate, Pediococcus pentosaceus C4/1A via continuous cultivation - Raman, Sasirega (2017)
Phytase enzyme is widely distributed in animals, plants and microorganisms which help in the degradation of phytate. Among the microorganisms, members of lactic acid bacteria (LAB) such as Pediococcus pentosaceus were found to produce phytase enzyme. The production of phytase in this study was identified by qualitative and quantitative enzyme assay. Qualitative assay was done by cultivation of the strains on modified MRS agar which contains MOPS and sodium phytate to observe the presence of clear halo zone, which indicates the enzyme production. Quantitative test was carried out to identify the highest phytase producer by cultivation of all the five isolates in modified MRS broth in shake-flask. The highest phytase producer was then selected and identified as Pediococcus pentosaceus C4/1A for conventional screening process based on medium formulation and culture conditions using Erlenmeyer shake-flask. Different nitrogen sources (peptone with casein, meat extract, yeast extract), carbon sources (glucose, maltose, lactose), different concentration of sodium phytate and inoculum size were determined on phytase production. From the study, yeast extract (20 g/L), glucose (15 g/L), sodium phytate (5 g/L) and inoculum size (5% (v/v)) gave effect on the phytase production by P. pentosaceus C4/1A. Further optimization by using Response Surface Methodology (RSM) was carried out on phytase production and cell biomass. The standardized protocol for phytase production was carried out in large scale using 2L stirred tank bioreactor. Formulated medium with glucose (16.2 g/L), yeast extract (17.2 g/L), sodium phytate (11.8 g/L) and inoculum size (10% (v/v)) were used to obtain high phytase activity. Continuous cultivation was then conducted for mass production and to determine the productivity of microbial biomass and production of phytase. Different range of dilution rate (D) was applied for 48 h to study the productivity of the cell and phytase. Secondary data based on phytase production, cell concentration and substrate consumption in small scale and large scale cultivation was developed and compared. Generally, all the chosen strains grew well on the modified MRS broth, however only one best phytase producer (P. pentosaceus C4/1A) exhibits highest enzyme activity of 21.25 U/mL. Further improvement through approach of RSM, 42.3 U/mL of phytase production was achieved with cell concentration of 6.46 g/L. Production of phytase then applied in large scale fermentation using 2L stirred tank bioreactor and 40.2 U/mL of phytase was synthesized by P. pentosaceus C4/1A, which comparable to the shakeflask cultivation (42.3 U/mL) under the optimized conditions. Continuous cultivation was carried out for mass production at dilution rate ranging from 0.1 h-1 to 0.4 h-1 and the steady state of P. pentosaceus C4/1A was achieved after five generation and three residence times. The whole process of cultivation was carried out for 48 h and the highest productivity of phytase and cell concentration was obtained at dilution rate 0.3 h-1 which resulted 8.65 U/mL/h and 0.894 g/L/h, respectively. In conclusion, throughout the cultivation process, production of phytase was improved 89.3% from shake-flask experiment to 2L bioreactor. In future work, scaling-up study for mass production at large scale should be performed as the application of phytase is of great interest in many industries.